A Review: Fracture Structure of Natural Fiber Surface after Treatment with Various Alkali Chemicals - Herlina Sari, Nasmi; Sari, Suteja; Sutaryono, Yusuf Akhyar; Khan, Moonish Ali (Green Engineering Society, 2024)
Natural fibers, including both animal and plant fibers, have many applications in a variety of sectors, therefore knowing the effects of chemical treatments on their characteristics is critical. This study evaluates the impact of different chemical treatments, including silanes, acetylation, benzoylation, peroxides, and several coupling agents, including maleation. In addition, this paper discusses treatment using acrylation and acrylonitrile, stearic acid, sodium chlorite, oleoyl chloride, isocyanate, and permanganate. These treatments alter the surface structure of the fibers by changing their chemical composition and shape. Silane and coupling maleation chemicals typically increase fiber attachment to the polymer matrix, whereas acetylation and benzoylation frequently improve resistance to moisture and microbial attacks. Peroxide and permanganate can produce oxidation, which reduces fiber strength, but grafting acrylation, acrylonitrile, and isocyanate improves resistance and temperature stability. Stearic acid and oleoyl chloride increase hydrophobicity, whereas sodium chlorite treatment alters the lignocellulose structure, increasing density and strength. This study also examines the impacts of biological treatment with fungi, that may change fiber structure via biodegradation pathways. This study's findings shed light on how various chemical treatments might alter the durability and strength of natural fibers, and also their use in industry and material technology.